RECUPERACIÓN DE LA VESTIMENTA TRADICIONAL DE LA PARROQUIA CACHA, MEDIANTE TALLERES EDUCATIVOS. - Melena Tingo, Margory Belen (2019)
The present research has a proposal to carry out cultural and educational revitalization. It aimed at children of the fifth and sixth years of Basic Education of the Intercultural Bilingual Educational Unit “Fernando Daquilema” through an educational workshop, which encourages student to see, perceive, assimilate and feel in a better way what the cultural richness is, valuing its importance and preservation on its customs, traditions, and clothing, throughout history it has become a local, national and international icon. Today young people are discriminated by other people, for the appearance of their clothing, place of origin which has influenced the way they act and dress, factors that have caused the loss of their identity and particularly the clothing, suffering a process of transculturation, assuming in some cases the definitive loss of attire. The methodology applied in the research is non-experimental because no variables were manipulated, the phenomenon was observed in a natural environment and educational context, obtaining information to be analyzed and acquired later; the type of research is qualitative, because it started proposing some definitions then developing certain fundamental aspects that involve the study of this community, it is an investigation of a social and educational nature, it was possible to have the setting of human activities to carry out the systematic and methodical search on the existing reality in the community of Shilpala parish of Cacha. The field researches were used, which allowed us to better understand the needs and desires of the inhabitants of the community, selecting each of the members involved in the research process. Conducting an exhaustive bibliographic review related to the object of study. It was established to organize and design educational workshops on the origin, history, culture, and tradition of the town of Cacha, it aimed at boys and girls of Basic Education, using fundamental theoretical references, achieving the interest of learning about their culture and especially to the conservation of their traditional clothing and then reach the respective conclusions.